Plasma and urine pharmacokinetics of hydroxyzine and cetirizine following repeated oral administrations to exercised horses. Issue 1 (1st September 2021) - Paine, Stuart W.; Aldurdunji, Mohammed; Garth‐Greeves, Alix; Muir, Tessa; Hincks, Pamela R.
Abstract: Hydroxyzine and cetirizine are first‐ and second‐generation oral antihistamine drugs, respectively, used to treat allergic reactions in horses. Cetirizine is also a metabolite of hydroxyzine, which may lead to complexities in regulating their use in equine sporting events. The aim of the research was to be able to provide detection times (DT) from pharmacokinetic studies in thoroughbred horses to better inform trainers, and their veterinary surgeons, prescribing these substances for treatment of Thoroughbred racehorses. Six and two horses were given 9 repeated administrations of hydroxyzine HCl (500 mg BID) or cetirizine HCl (190 mg BID), respectively. Plasma and urine hydroxyzine and cetirizine concentrations were measured by liquid chromatography–tandem mass spectrometry (LC‐MS/MS). A holistic non‐linear mixed effects PK model was developed that described both plasma and urine concentrations of hydroxyzine and cetirizine, either from administration of each individually or cetirizine as a metabolite of hydroxyzine. Using the parameters obtained from this PK model in conjunction with methodology developed by Toutain afforded possible screening limits (SL) that can regulate for a DT of 4 days in either plasma or urine. Hydroxyzine and cetirizine concentration prediction intervals for the 80 th, 95 th and 99 th percentiles of a virtual horse population were performed in order to assess the statistical protection of the DT. However, it is down to the individual racing authorities to apply their own risk management.